Evaluating Optical Backhaul of a Fiber and Wireless Hybrid Broadband Network - Lee, Weng Hong (2015)
The backhaul for a fiber and wireless (FiWi) hybrid broadband network is an optical network system. It deployed the optical fiber instead of copper wire for the connection in this system. This fiber sub-network provides large bandwidth and high speed rate compare to the copper wire system. This is achieved due to the use of light in the transmission medium of the optical network system. The major components used in the optical network system are optical line terminal (OLT), splitter, optical network terminal (OLT), optical fiber cables and connectors. OLT is usually located at the centre office (CO) and connected via optical fiber to several optical network terminals (ONT) through optical splitters. The optical network system chosen in this project was Fiber To The Home (FTTH). An Ethernet Passive Optical Network (EPON) for FTTH was configured for evaluating its performance for transmission of data and video content.